1999
DOI: 10.1200/jco.1999.17.2.460
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Breast Cancer Patients With Complete Pathologic Primary Tumor and Axillary Lymph Node Response to Doxorubicin-Based Neoadjuvant Chemotherapy

Abstract: Neoadjuvant chemotherapy has the capacity to completely clear the breast and axillary lymph nodes of invasive tumor before surgery. Patients with LABC who have a pCR in the breast and axillary nodes have a significantly improved disease-free survival rate. However, a pCR does not entirely eliminate recurrence. Further efforts should focus on elucidating the molecular mechanisms associated with this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

51
709
8
33

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,214 publications
(801 citation statements)
references
References 31 publications
51
709
8
33
Order By: Relevance
“…Another publication with a large number of patients treated in two prospective randomised trials utilised the classification system proposed by Kuerer et al (1999). This has three grades; no evidence of residual disease, o1 cm 3 of macroscopic residual tumour (residual microscopic foci of cancer cells included) and 41 cm 3 of residual macroscopic tumour (Kuerer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another publication with a large number of patients treated in two prospective randomised trials utilised the classification system proposed by Kuerer et al (1999). This has three grades; no evidence of residual disease, o1 cm 3 of macroscopic residual tumour (residual microscopic foci of cancer cells included) and 41 cm 3 of residual macroscopic tumour (Kuerer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This has three grades; no evidence of residual disease, o1 cm 3 of macroscopic residual tumour (residual microscopic foci of cancer cells included) and 41 cm 3 of residual macroscopic tumour (Kuerer et al, 1998). These investigators analysed 372 patients with locally advanced breast cancer treated with four cycles of neoadjuvant chemotherapy in two prospective randomised studies (Kuerer et al, 1999). Of these patients, 43 (12%) had no histological evidence of residual invasive carcinoma in both breast and axillary nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all neoadjuvant chemotherapy trials demonstrated that survival was correlated with the response to neoadjuvant chemotherapy with survival rates ranging from 85% to 90% for patients with complete breast tumor and lymph node response. 3,33,34 Conversely, patients with no response displayed poor survival. It could be hypothesized that with the regimens of chemotherapy used in the historical randomized trials, two populations can be individualized, namely, one population best treated with preoperative chemotherapy and one best treated with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%